PERLINDUNGAN KONSUMEN TERHADAP PENJUALAN IPAD TANPA BUKU PETUNJUK BERBAHASA INDONESIA DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 - Poltak Siringoringo (to-ra, 2019)
Abstract At present the need for electronic goods has become a primary need. There is no denying that electronic equipment helps in human life. Some are used as entertainment tools and some are used as work aids. But there are also those that can be used as well as work tools and entertainment, even educational facilities. This need does not mean insigniï¬cant, because as a civilized human being, living in a community is in dire need of various other things that are broader and perfect, both regarding the quality, quantity, and type. It is not surprising then that the industry is rapidly advancing because the level of market needs is quite high, but electronic products include products that have speciï¬city so that not all consumers can know the ins and outs, both capabilities, quality, instructions for use, guarantees / guarantees, after sales service and so on. The fact shows that Indonesia has grown and developed many industrial goods and services, both large and small scale, especially since the implementation of national development in stages and planned through a ï¬ve-year development plan. Keywords: human life; national develpoment; facilities.